La réflexivité comme instrument de formation par l’alternance et de développement de l’activité professionnelle des enseignants - Stefano Bertone; Frédéric Saujat (Activités)
This study is part of a research program to provide on-going assessment of the reforms in teacher training currently underway in France. The focus of this particular study was on the training conditions which optimize preservice teachers’ reflective analysis of their work. The results showed that the professional activity of preservice teachers develops as they restructure the meaning of their experience through two processes: (a) the mobilization of professional concepts learned during training interactions and (b) the affects that they experience in self-confrontation interviews which provoke a greater awareness of their concerns and a remobilization of the concepts learned during post-lesson interviews.